PROGRAM APLIKASI PERPUSTAKAAN MENGGUNAKAN JAVA NETBEANS 8.0.2. DAN CATALOGUE ONLINE DENGAN DATABASE MYSQL (Jurnal Informatika Terpadu, 2017)
The application program is designed for library, especially for library automation with data entry facilities of library materials and book member data entry and search facilities Online Public Access Catalogue (OPAC). This materials install program focused on servers, databases, interfaces and demonstration of existing facilities.